2013
DOI: 10.1186/1710-1492-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Improper inhaler technique is associated with poor asthma control and frequent emergency department visits

Abstract: BackgroundUncontrolled asthma remains a frequent cause of emergency department (ED) visits and hospital admissions. Improper asthma inhaler device use is most likely one of the major causes associated with uncontrolled asthma and frequent ED visits.ObjectivesTo evaluate the inhaler technique among asthmatic patients seen in ED, and to investigate the characteristics of these patients and factors associated with improper use of inhaler devices and its relationship with asthma control and ED visits.MethodsA cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
205
1
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(229 citation statements)
references
References 28 publications
11
205
1
12
Order By: Relevance
“…It has been reported that most children and adults reduce their mistakes in inhalation device use after getting education about it (31,32). Repeated educations result in better inhalation technique and play a key role in successful inhalation therapy (8,9,22,23,25,30,31). It is reported that repeated education about MDI inhalation technique resulted in a statistically significant improvement in MDI technique scores when compared to single education (33,34).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…It has been reported that most children and adults reduce their mistakes in inhalation device use after getting education about it (31,32). Repeated educations result in better inhalation technique and play a key role in successful inhalation therapy (8,9,22,23,25,30,31). It is reported that repeated education about MDI inhalation technique resulted in a statistically significant improvement in MDI technique scores when compared to single education (33,34).…”
Section: Resultsmentioning
confidence: 77%
“…Improvement in MDI technique provides better delivery of medication into the lungs thus clinically significant improvement (11). Inappropriate inhalation technique decreases drug delivery in the lungs and decreases the efficacy of medical treatment and hinder better asthma control (7,8,10,11). People with asthma and improper inhaler technique were shown to have poorer symptom control compared to those with good inhaler technique, with a subsequent increase in medical or emergency visits (8,11,20,25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case the average use over time is meaningless unless data on the technique of use is also incorporated into the calculation of the adherence. Most electronic recording devices usually do not assess if the inhaler was taken correctly (5)(6)(7)(8)(9)(10)(11)(12). Hence, there is a need to develop a method to quantify adherence that accounts for variations in dosing schedules as well as inhaler user technique.…”
mentioning
confidence: 99%
“…81,82 Poor inhaler technique has been associated with poor outcomes. 83 The prescribed drug/device should be affordable and easily available at retail sale points. Licensed independent practitioners should discuss with the patient and family the different platform alternatives that are available for a specific treatment, and they should agree on a specific platform after having discussed the pros and cons.…”
Section: Challenge Of Matching Patient Drug and Devicementioning
confidence: 99%